L’uso strategico della comicità nel discorso politico di Silvio Berlusconi - Miłkowska-Samul, Kamila (Wydawnictwo Naukowe UAM, 2013)
The aim of this article is to illustrate some of the mechanisms existing in political discourse which employ emotions and humor as a persuasive means. The study is based on authentic texts produced by Silvio Berlusconi. The importance of emotions and humor in political speech is viewed in the light of changes taking place in public communication due to the development of mass media and Internet, leading to, among others, ever more frequent use of the comical aspect of communication as a method of gaining and maintaining political power. That is why the use of emotions and humor in Berlusconi’s speech is analyzed as a strategic choice and a powerful instrument of political struggle. The article highlights the role of emotions and humor in creating a positive self-image of the politician.
The strategic use of humor in political discourse of Silvio Berlusconi
Keywords: political discourse; political struggle; emotions; humor